Preparation of Interactive CD-ROM on Poultry farming and Assessment of Its Effectiveness (Indian Journal of Extension Education, 2014)
Interactive CD-ROM using flash was prepared as per standard procedures. Accuracy, Coverage, Objectivity, Content presentation, Layout and Suitability of pictures, write up and compatibility of CD was perceived high for all the messages on all the parameters Thus it clearly indicates that all the messages were clearly stated, self explanatory and information